Asymmetric effects of financial and technological development on green energies: Evidence from solar, wind and renewable electricity with an emphasis on crisis conditions - Fariba Osmani; Taghi Ebrahimi Salari (Results in Engineering)
The transition to renewable energy is a global priority. Therefore, the present study aims to analyze the asymmetric effects of technological and financial development on the development of renewable energy resources in four groups: total renewable energy, renewable electricity, solar and wind energy, with a focus on crisis conditions in 23 European countries. This analysis is conducted using the nonlinear autoregressive distributed lag (NARDL) new method. The results of the regression estimates emphasize that a positive fiscal shock in the long run helps the development of solar and wind energy, while it does not affect the development of renewable electricity. Furthermore, the results show that the positive technology shock in the long run contributes to the increase in renewable electricity and solar energy, while it does not have a significant effect on the development of wind energy. Policy implications emphasize the pivotal role of technology for the development of renewable and solar electricity due to its large-scale economies, especially in the face of crises, in shaping a sustainable and resilient energy future. While previous studies focused on the effects of technological and financial development on renewable energy consumption, they neglected to examine the positive and negative shocks of technological and financial development on each renewable energy source. Therefore, the innovation of the present article is to focus on presenting the technological and financial level appropriate to each renewable source and to provide recommendations for the development of green energy infrastructures by storing financial resources and integrating technologies, especially in crisis situations.